2007
DOI: 10.1111/j.1365-2389.2006.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic nitrogen and carbon in pastoral soils: the New Zealand experience

Abstract: Dissolved organic nitrogen (DON) and dissolved organic carbon (DOC) in soils are increasingly recognized as important components of nutrient cycling and biological processes in soil-plant ecosystems. The aims of this study were to: (i) quantify the pools of DON and DOC in a range of New Zealand pastoral soils; (ii) compare the effects of land use changes on these pools; and (iii) examine the seasonal variability associated with these two components of dissolved organic matter. Soil samples (0-7.5 cm depth) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 39 publications
2
39
0
1
Order By: Relevance
“…texture or organic content play an important role on N losses. Recently, researchers have put more emphasis on studying the contribution of dissolved organic nitrogen (DON) to the N balance of landscapes (Mattson et al, 2009;Cooper et al, 2007;Ghani et al, 2007;van Kessel et al, 2009;Neff et al, 2003. Hedin et al (1995) found that organic N represents a large part of the total N losses from forest ecosystems, which was also described in other studies (van Breemen, 2002;Cooper et al, 2007;van Kessel et al, 2009;Neff et al, 2003.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…texture or organic content play an important role on N losses. Recently, researchers have put more emphasis on studying the contribution of dissolved organic nitrogen (DON) to the N balance of landscapes (Mattson et al, 2009;Cooper et al, 2007;Ghani et al, 2007;van Kessel et al, 2009;Neff et al, 2003. Hedin et al (1995) found that organic N represents a large part of the total N losses from forest ecosystems, which was also described in other studies (van Breemen, 2002;Cooper et al, 2007;van Kessel et al, 2009;Neff et al, 2003.…”
mentioning
confidence: 81%
“…Due to the same organic matter origin and similar organic components, DON is often closely linked to the C cycle (Campbell et al, 2000;Cooper et al, 2007;Ghani et al, 2007;Goodale et al, 2000;van Kessel et al, 2009;Willett et al, 2004). Accordingly, it is assumed that DON and DOC should be equally influenced by soil type or land use.…”
Section: Dissolved Organic Carbon (Doc)mentioning
confidence: 99%
See 1 more Smart Citation
“…SMBC and SMBN were calculated as: SMBC or SMBN = (total C or N in fumigated extractsÀtotal C or N in unfumigated extracts)/K E , where K E = 0.45 (Wu et al, 1990;Jenkinson, 1988). DOC was the amount of TOC in the unfumigated extract (Cookson et al, 2007;Ghani et al, 2007) and DON was the difference between N and NH 4 -N in unfumigated extracts (Cookson et al, 2007;Ghani et al, 2007). Soil carbonate C was determined by the pressure calcimeter method (Loeppert and Suarez, 1996).…”
Section: Measurementsmentioning
confidence: 99%
“…DON significantly contributes to N leaching losses from forest ecosystems (Campbell et al 2000;Qualls et al 2000;Perakis and Hedin 2002), and may be an important form of N losses from agricultural systems (Murphy et al 2000;McDowell 2003;Siemens and kaupenjohann 2002;Saarijarvi et al 2007). Compared to NO 3 -N, there are only a limited number of studies on DON leaching losses from agricultural soils (Ghani et al 2007;Kessel et al 2009). On average, the amount of DON leaching losses from agricultural systems was estimated to be approximately one-third of that of NO 3 -N (Kessel et al 2009).…”
Section: Introductionmentioning
confidence: 99%